Analysis of structural concrete bar members based on secant stiffness methods - Al-Rumaithi, Ayad; Fadhil, Aqeel T.; Salman, Ban Fadhil (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the behavior of structural concrete linear bar members was studied using numerical model implemented in a computer program written in MATLAB. The numerical model is based on the modified version of the procedure developed by Oukaili. The model is based on real stress-strain diagrams of concrete and steel and their secant modulus of elasticity at different loading stages.
Keywords: secant stiffness; numerical modeling; prestressed; structural concrete